2014
DOI: 10.1021/cm5026987
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Specific Biomolecule Adsorption on Silica Surfaces as a Function of pH and Particle Size

Abstract: Silica nanostructures are biologically available and find wide applications for drug delivery, catalysts, separation processes, and composites. However, specific adsorption of biomolecules on silica surfaces and control in biomimetic synthesis remain largely unpredictable. In this contribution, the variability and control of peptide adsorption on silica nanoparticle surfaces is explained as a function of pH, particle diameter, and peptide electrostatic charge using molecular dynamics simulations with the CHARM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
170
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 128 publications
(185 citation statements)
references
References 75 publications
(239 reference statements)
12
170
0
1
Order By: Relevance
“…The parameters were integrated into several FFs (AMBER, CHARMM, COMPASS, INTERFACE ) compatible with the TIP3P and SPC water models. In particular, the CHARMM-INTERFACE FF ) was applied to simulation of peptide adsorption on silica nanoparticles of different size at different pH values (Emami et al 2014b), showing good agreement of nanoparticle coverage with experimental data (Puddu & Perry, 2012).…”
Section: (2012)mentioning
confidence: 89%
See 4 more Smart Citations
“…The parameters were integrated into several FFs (AMBER, CHARMM, COMPASS, INTERFACE ) compatible with the TIP3P and SPC water models. In particular, the CHARMM-INTERFACE FF ) was applied to simulation of peptide adsorption on silica nanoparticles of different size at different pH values (Emami et al 2014b), showing good agreement of nanoparticle coverage with experimental data (Puddu & Perry, 2012).…”
Section: (2012)mentioning
confidence: 89%
“…Particularly, SMD simulations conducted to investigate the effect of the tip of an AFM showed that pushing a molecule towards a surface with an AFM tip will bias the results by increasing adhesion, as the force exerted on the molecule leads it to spread more on the surface (Horinek et al 2008;Mücksch & Urbassek, 2011). With SMD simulations, the adsorption mechanisms of peptides and proteins on different types of surfaces have been investigated (Alvarez-Paggi et al 2010;Dong et al 2007;Emami et al 2014b;Friedrichs et al 2013;Hamdi et al 2008;Shen et al 2008;Utesch et al 2011;Yang & Zhao, 2007) and compared with experimental measurements (Schneider & Colombi Ciacchi, 2010. In addition to accelerating the sampling of certain events, the SMD method is used to calculate free energy differences.…”
Section: Non-equilibrium Methodsmentioning
confidence: 99%
See 3 more Smart Citations